Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/clinpract13010010
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox 2022 Outbreak: How Alarming Is the Situation? Epidemiological and Clinical Review

Abstract: Monkeypox is a disease caused by Orthopoxvirus, which also includes the smallpox virus. Several endemics have been reported on the African continent, typically in the western and central regions. However, since 13 May 2022, there have been several cases reported from different member states; the number of confirmed cases in 1 month exceeded the total number of cases reported outside the African continent since the first case in 1970. The World Health Organization (WHO) and Centers for Disease Control (CDC) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…Secondly, despite its primary association with primates, it can infect various animal and human species [ 2 ]. Unlike the outbreaks in humans in past decades [ 4 ], the 2022 epidemic outbreak constitutes the first significant case of global dispersion, affecting several countries and continents [ 5 ]. Third, the global discontinuation of vaccination programs against orthopoxviruses (i.e., vaccinia virus vaccine) after the eradication of smallpox potentially correlates with the re-emergence of this virus [ 7 ], implying the need to review global vaccination strategies to prevent or control new outbreaks of HMPX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, despite its primary association with primates, it can infect various animal and human species [ 2 ]. Unlike the outbreaks in humans in past decades [ 4 ], the 2022 epidemic outbreak constitutes the first significant case of global dispersion, affecting several countries and continents [ 5 ]. Third, the global discontinuation of vaccination programs against orthopoxviruses (i.e., vaccinia virus vaccine) after the eradication of smallpox potentially correlates with the re-emergence of this virus [ 7 ], implying the need to review global vaccination strategies to prevent or control new outbreaks of HMPX.…”
Section: Discussionmentioning
confidence: 99%
“…The first instance of HMPX outside Africa was reported in 2003 in the United States, with 47 cases. Between 2000 and 2020, a total of 20,237 cases of HMPX were reported across 16 countries [ 4 ]. Although MPXV had been primarily confined to African countries with occasional outbreaks elsewhere, in May 2022, a case of HMPX was documented in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…11 John et al, (2022) reported that the first case was found in the outer region of Africa and later identified upto 528 active cases between April, 27 to June 24, 2022 in 43 different cities in sixteen different countries. 4,12 Ninety eight percent (98%) were found in gay and bisexual men. Moreover, seventy five percent (75%) were found in white population while forty one percent (41%) were found in immunocompromised patients such as affected with Immunodeficiency Virus (HIV) infected individuals.…”
Section: Monkeypox Impact On the Health Of The World Communitymentioning
confidence: 99%
“…Though previously a relatively rare disease isolated to portions of western and southern Africa, a cluster of cases linked to communities of men who have sex with men (MSM) in parts of Europe and the United States implicated disease spread to communities previously unaffected by the virus [ 2 ]. After cases spread to children and adults, regardless of demographics [ 3 ], it became clear that interhuman transmission was responsible for most new cases, prompting renewed concerns of a follow-up uncontrollable disease [ 4 ].…”
Section: Introductionmentioning
confidence: 99%